2020
DOI: 10.1177/8756087920910481
|View full text |Cite
|
Sign up to set email alerts
|

High performance epoxy/polyester-based nanocomposite coatings for multipurpose applications: A review

Abstract: Epoxies are important thermosetting polymers with exceptional features, which have been successfully employed for coatings. Polyester blends with epoxy enhances their chemical inertness, anti-rusting, toughness, strength, glass transition temperature, and heat stability, Epoxy/polyester blends have been further reinforced with nanocarbon, nanoclay, and inorganic nanoparticles to form nanocomposite coatings. Incorporating nanoparticles in epoxy/polyester has further improved their engineering properties. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 86 publications
0
10
0
Order By: Relevance
“…This indicates the nanofiller and polymer network is compatible. 1 Morphological analysis. Figure 3 has PVTZ and PVTZ/TiO 2 composite SEM micrographs.…”
Section: X-ray Diffraction Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates the nanofiller and polymer network is compatible. 1 Morphological analysis. Figure 3 has PVTZ and PVTZ/TiO 2 composite SEM micrographs.…”
Section: X-ray Diffraction Studiesmentioning
confidence: 99%
“…Present research on polymer hybrid coatings is increasing applications for corrosion control. 1,2 Incorporating nanoparticles in a polymer matrix not only increases the thermal stability they also improve anticorrosive properties by increasing the path length of corrosive species. 3 Among different nanoparticles, TiO 2 NPs have been used widely because they are non- toxic, cheap and easy to prepare.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer coatings are found in a variety of application areas, from food packaging [1][2][3] and automotive paints [4][5][6][7][8] to corrosion prevention [9][10][11][12][13][14] and material decontamination. [15][16][17][18][19][20][21] One of the DOI: 10.1002/marc.202300304 primary functions of coatings is to protect the underlying substrate against external agents, such as solvents, [22][23][24] toxins, [25,26] bacteria, [27][28][29][30][31][32] or corrosive ions, [33][34][35][36][37][38][39] that are harmful to the underlying surface.…”
Section: Introductionmentioning
confidence: 99%
“…26 Compared with CTBN, the linear carboxylterminated polyester has better oxidation stability because it does not contain unsaturated structure, and the polyester material is generally nontoxic, which is in line with the concept of green development. The reports on polyester modied epoxy resin mainly focus on unsaturated polyester and hyperbranched polyester, [27][28][29] while the reports on linear saturated polyester are less. Achary et al 30 modied epoxy resin by carboxyl-terminated poly (propylene adipate) glycol ester (CTPPGA), found that the modied epoxy resin adhesive strength depends on the molecular weight and content, and the epoxy resin adhesive can be used at 120 C. Ratna et al 26 used carboxyl-terminated polyethylene glycol adipate (CTPEGA) as toughening agent, reacted with epoxy resin to form epoxy-terminated prepolymer.…”
Section: Introductionmentioning
confidence: 99%